(untitled) (Update Dental College Journal, 2017)
Introduction: The fabrication of dental prosthesis requires the transfer of interocclusal records from patient’s mouth to an articulator using different kinds of recording materials. Any inaccuracy in these interocclusal records leads to occlusal error in the final prosthesis. Interocclusal recording materials should have good dimensional stability for precise articulation. Purpose: The aim of this in vitro study was to evaluate and compare the dimensional stability of two types of interocclusal recording materials at various time intervals. Materials and Methods: The materials used in this study were polyvinylsiloxane (Reprosil Silicone Putty) and alginate (irreversible hydrocolloid). In this experimental study, specimen of polyvinylsiloxane and alginate were prepared from a custom made stainless steel die according to ADA specification no-19, in the form of a disk included three parallel lines on the surface which were provided as an indicator to see the dimensional stability of tested materials. The distance between parallel lines was measured at two fixed points using a traveling micrometer microscope. A total of 20 samples were made from group-A and group-B consisting of ten samples of each group. The measurements were made at time intervals of 1, 24, 48 and 72 hrs. Results: Two readings were taken for each sample at each time interval and the mean was considered to measure the dimensional change by comparing with that of the original measurements in the die. The results obtained were statistically analyzed using SPSS version 12 and paired t test. The result of significance was expressed as p value. P value <0.05 was considered as significance. Both materials showed significant changes ie <0.05. Conclusion: Dimensional stability is influenced by both the material used and the time factors and was found to decreased dimensional stability as the time factors increased. Group A was dimensionally stable than Group-B. Update Dent. Coll. j: 2017; 7 (1): 10-13